Highly sensitive and selective assay method for iodide ion determination based on gold nanoparticles conjugated with glycol chitosan - Kim, Kyung Min; Nam, Yun-Sik; Lee, Yeonhee; Lee, Kang-Bong (TAYLOR & FRANCIS LTD, 2017)
A sensitive colorimetric method for the determination of iodide ions was developed using gold nanoparticles (AuNPs) functionalised with glycol chitosan (GCS). The iodide ions were at the centre of the O-I--O coordination structure, formed with the GCS-AuNPs, reducing their interparticle distance and inducing aggregation. Time-of-flight secondary ion mass spectrometry analyses showed that the bound iodide ions were coordinated to the oxygen atoms of the ethylene glycol in GCS, with this aggregation leading to a considerable variation in colour from light red to dark violet. Using this GCS-AuNP probe, the iodide ion concentration in environmental, biological and pharmaceutical samples could be determined by both the naked eye and UV-Vis spectroscopy. Additionally, the sensitivity of the detection was found to be markedly enhanced at pH 6, where a more pronounced colour change was observed. The absorption ratio A(700)/A(521) of the functionalised AuNP solution correlated linearly with the iodide ion concentration within the range 0.0-10.0mg/L, and the limits of detection in tap water, pond water, and bovine serum solution were 3.5, 3.6, and 3.4g/L, respectively. The present assay method can thus be utilised to rapidly measure the concentration of iodide ions in aqueous samples.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY; PLASMA-MASS SPECTROMETRY; COLORIMETRIC DETECTION; SILVER NANOPARTICLES; FLUORESCENT-PROBES; DEFICIENCY; PREGNANCY; GROWTH; SENSOR; SPECIATION